2017
DOI: 10.2106/jbjs.16.00514
|View full text |Cite
|
Sign up to set email alerts
|

Familial Clustering Identified in Periprosthetic Joint Infection Following Primary Total Joint Arthroplasty

Abstract: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Although the FSIR and RR are dependent on several factors, including the prevalence of the disease in the population, our data are consistent with other studies examining the potential genetic contribution to other familial diseases using the UPDB. [43][44][45][46] Thus, the main finding of this study was that Kienböck's disease clusters in families within a large population-based cohort, which suggests that there may be a genetic basis to the etiology of this disease.…”
Section: Discussionmentioning
confidence: 65%
“…Although the FSIR and RR are dependent on several factors, including the prevalence of the disease in the population, our data are consistent with other studies examining the potential genetic contribution to other familial diseases using the UPDB. [43][44][45][46] Thus, the main finding of this study was that Kienböck's disease clusters in families within a large population-based cohort, which suggests that there may be a genetic basis to the etiology of this disease.…”
Section: Discussionmentioning
confidence: 65%
“…Familial susceptibility for the development of an SSI and increased susceptibility for PJI of patients whose relative have had a PJI have been reported. 75,76 Few studies have investigated gene polymorphisms where multiple small nucleotide polymorphisms (SNPs) in the mannose-binding lectin (MBL) gene, which has a role in opsonization and mediates complement activation, have increased risk for PJI.…”
Section: Geneticsmentioning
confidence: 99%
“…Wound complications were assessed in 13 cohort studies ( 10 , 14 , 15 , 19 , 20 , 41 , 45 48 , 55 57 ) and seven case-control studies ( 16 , 24 , 34 , 38 , 39 , 42 , 58 ) involving 706,107 patients. Meta-analysis showed that smoking increased the risk of wound complications after THA and TKA ( OR 1.77, 95% CI 1.50–2.10; I 2 = 85%; Table 2 ).…”
Section: Surgical Complicationsmentioning
confidence: 99%
“…Data on prosthetic joint infection were extracted from eight cohort studies ( 10 , 20 , 41 , 46 48 , 56 , 57 ) and six case-control studies ( 24 , 34 , 38 , 39 , 42 , 58 ) involving 234,937 patients. Meta-analysis showed that patients who smoked were at higher risk of prosthetic joint infection than patients who did not ( OR 1.84, 95% CI 1.52–2.24; I 2 = 63%; Table 2 ).…”
Section: Surgical Complicationsmentioning
confidence: 99%